PEMASARAN MELALUI E-COMMERCE PADA UMKM DI DESA EKANG ANCULAI - Muqtafin, Muqtafin; Alfi Hendri; Maryati, Maryati; Hendy Satria; Senddy Febrianto; Diana Try Cahyani Nala (Bajang Institute, 2025)
E-commerce, or electronic commerce, refers to the process of dissemination, purchase, sale, and marketing of goods and services through electronic systems such as the internet, television, www, or other computer networks. This includes electronic fund transfers, electronic data exchange, automatic inventory management systems, and automatic data collection systems. In the context of the Real Work Lecture (KKN), students are tasked with innovating and digitizing Micro, Small, and Medium Enterprises (UMKM) to promote community self-reliance. One of the challenges faced is the underutilization of digitalization by UMKM entrepreneurs in sales activities. Therefore, we directly engage in the field to assist UMKM entrepreneurs in promoting their products through the Shopee application. The main objective of this KKN activity is to facilitate the creation of Shopee application accounts so that UMKM entrepreneurs can quickly utilize the platform to market and promote their products to the wider community. Through the establishment of Shopee accounts, it is hoped that competitiveness will increase and challenges faced by UMKM in digital marketing will be addressed. Furthermore, it is anticipated that this initiative will contribute positively to the local economy in Ekang Anculai Village, Teluk Sebong District, Bintan Regency.